Coerción sorda de las relaciones económicas: Aplicación de un concepto marxista para comprender las relaciones de producción en la hacienda andina - Gascón, Jorge (Sociedad y Economía, 2005)
The present paper intends to contribute to the development of Marx’s concept of deaf coercion of economic relations. As used The Capital, it allows him to explain how the capacity of control of the capitalist systems over the working class is executed through infrastructural factors. In the context of this paper the concept is applied to the Latin American hacienda system and, concretely, to the Andean system. The purpose is to show the richness and universality of the concept, which also can be used as a theoretical basis for delving into the knowledge of control mechanisms existing within the relations of production that diverge from those to which the concept has been applied up to now.